Research status and prospect of peri‐extubation delirium. Issue 3 (28th September 2021) - Jiang, Rui; Zhu, Yi; Zhu, Yu‐Hang; Zhu, Zhao‐Qiong
Abstract : Peri‐extubation delirium is a clinical syndrome caused by multiple factors, and it is not a simple disease. It occurs within a period of time after extubation when the effect of general anesthesia is reduced. And the incidence is different in disparate populations, and it is more common in elderly patients. Current studies have shown that iatrogenic factors and patients' own factors are the main risk factors for the syndrome. Early identification of risk factors can help clinicians make early diagnosis. The earlier the diagnosis and treatment begin, the more significantly the prognosis of patients can be improved. At present, the treatment of perioperative delirium is based on non‐drug therapy, supplemented by drug therapy. This review will introduce in detail the risk factors, population status and prevention measures of delirium during peri‐extubation, and look forward to the new research direction in the future.